DIET COMPOSITION AND FEEDING HABITS OF NAUJAN WHITE GOBY (Glossogobius aureus) IN NAUJAN LAKE, PHILIPPINES - Elsie Guibone; Katherine Sanchez-Escalona; Abelle Balagtas; Fritz Dustin Fiedalan; Kidelyn Lomio (SEAMEO BIOTROP, 2025)
ARTICLE HIGLIGHTS- The Naujan White Goby (Glossogobius aureus) is an economically important commodity, valued locally for dried fish, making it vulnerable to overexploitation.- Domestication efforts attempt to lessen fishing pressure while conserving wild populations; however, the feeding ecology of this native fish in Naujan Lake is still unknown.- Understanding Glossogobius aureus’ diet composition and feeding habits from its natural habitat is critical for establishing its culture.Glossogobius aureus is a benthic carnivore that feeds primarily on shrimp, followed by fish and other prey items.ABSTRACTNaujan White Goby (Glossogobius aureus), commonly processed as dried fish, is a local delicacy in Oriental Mindoro, Philippines. However, the product’s growing popularity and rising demand have raised concerns about the overexploitation of this economically valuable species. While efforts to domesticate G. aureus have been initiated as a conservation measure, information on its feeding ecology in Naujan Lake National Park is lacking. This study investigated the diet composition, feeding habits, feeding intensity, and seasonal and site-based variations in the diet of G. aureus in Naujan Lake by monthly sampling from February 2020 to January 2021. A total of 1,938 G. aureus comprising 1,094 males and 844 females were collected, ranging from 75 mm to 280 mm in total length. Glossogobius aureus is a benthic carnivore. Shrimp forms the bulk of its diet, followed by fish and other prey. Occasional opportunistic feeding was observed in June to August when the usual prey were scarce. Pairwise comparison showed a significantly high percentage occurrence of shrimp observed during the dry months (January to March) and rainy months (September to November) compared to the lowest ingestion recorded in June and July (P < 0.05). The dietary patterns varied significantly across the six sampling sites and seasonal periods. Feeding intensity was the highest before spawning and declined during the spawning period. Males exhibited greater feeding activity compared to females. The findings offer valuable insights into the feeding patterns of G. aureus, which could help optimize dietary strategies for its successful culture in captivity.